Diseño de una ruta aviturística en la parroquia Pujilí, Cantón Pujilí de la Provincia de Cotopaxi. UTC. Latacunga. - Quimbita Molina, Blanca Elizabeth (2022)
In the parish of Pujilí several wildlife inventories have been developed, unfortunately, this has not been adequately exploited; therefore, this research proposed to make a bird watching route that integrates several sectors of the parish, providing an alternative for those who visit the parish throughout the year. Thus, a diagnosis of the study area was proposed, through the review of bibliographic information some conditions of the place were established, whose altitudinal range varies from 2933 m.a.s.l. to 3018 m.a.s.l., it has characteristics such as crops and vegetation that provide food and shelter so nine study areas were identified, both in urban and rural areas. In addition, there are four natural and cultural attractions in the parish, and the tourist plant was identified. Subsequently, the need for a bird inventory was determined, because several of the sites did not have a bird registry; This was done through direct observation, point counts and intensive search, identifying through technological tools (Ebird and GPS) a total of 22 species, divided into 6 orders, 14 families, of which the most predominant within the parish was the Passeriform order with more than 50% representation in all areas and a decrease in the other orders, noting that all species are in a state of conservation of minor concern. For the selection of the sites that will make up the route, the situation of the tourist plant was analyzed, as well as the application of the Sorensen index, to verify the similarity of the areas where the inventory was carried out, of which the highest percentages were verified and progressively compared, so that only five of the nine initial zones were considered for the route. With this, a route was designed, consisting of 5 bird observation points, over a distance of 15km. It is suggested that the route be completed in one or two days, the time required to complete it is 11 hours in the first case and 6 hours per day in the second. Finally, it is hoped that the route can be used by local people to promote birdwatching and environmental conservation.